Clevidipine and COVID 19: From Hypertension to Inflammatory Response - Guerrero Orriach JL; Quesada Muñoz G (Dove Medical Press, 2022)
Jose Luis Guerrero Orriach,1- 3 Guillermo Quesada Muñoz1- 3 1Institute of Biomedical Research in Malaga, Malaga, Spain; 2Department of Anesthesiology, Virgen de la Victoria University Hospital, Malaga, Spain; 3Department of Pharmacology and Pediatrics, School of Medicine, University of Malaga, Malaga, SpainCorrespondence: Jose Luis Guerrero Orriach, Institute of Biomedical Research in Malaga, Malaga, Spain, Email guerreroorriach@gmail.comAbstract: Globally, more than 4 million have died from COVID-19, World Health Organization (WHO) to declare COVID-19 a pandemic. The COVID 19 pathology, produced by SARS-COV2, a virus from the coronavirus family, emerged at the end of 2019. The majority of cases usually have a mild or moderate form, characterized by fever, cough, intense asthenia and multiple symptoms derived from the initial replicative effect and subsequent hyperimmune effect. Severe cases present with Acute Respiratory Distress Syndrome (ARDS), due to pneumonia with bilateral involvement, which lead to hospital admission of patients and the need for admission to intensive care units (ICU) of approximately 10‒20%. According to the different series; the mortality of the condition once the patient is admitted to the ICU is close to 35‒45%. Currently, more than 4 million people have died in the world due to this pathology. The volume of infections generated the declaration by the World Health Organization (WHO) of the pandemic situation. Factors associated with a higher risk of progression into severe disease include age and comorbidities, especially systemic arterial hypertension due to its high incidence in the general population. Clevidipine can be rapidly and effectively adjusted to the clinical status of the patient, since it can be withdrawn and its effects reversed in just a few minutes, and contains high concentrations of lipids, and it could reduce the inflammatory response induced by SARS-COV2, which is key to progression into severe disease. However, its application in pro-inflammatory settings has not yet been explored, although it must play a key role in inflammation as a scavenger molecule.Keywords: clevidipine, COVID-19, hypertension, blood pressure, SARS-COV2